Effluent toxicity study using biomarkers for ciprofloxacin photoelectrocatalytic degradation by bismuth-doped titanium dioxide nanotubes - Oliveira, E M (Environmental technology, 2024)
Ciprofloxacin hydrochloride (CIP) is a broad-spectrum synthetic antibiotic often found in domestic sewage and industrial waste due to the inefficiency of conventional treatments. Given the potential risk of drug accumulation, this study presents coatings of titanium dioxide nanotubes (TiO2) doped with different bismuth (Bi) concentrations to degrade CIP through photocatalytic and photoelectrochemical processes. Characterization studies revealed that bismuth (Bi) doping affected the morphology of the materials, with concentrations of 0.01 and 0.05 mol L-1, resulting in collapsed materials with a smaller active surface area. Photocatalysis tests for all the materials exhibited a similar degree of efficiency to photolysis, approximately 33%. Ecotoxicity tests using the biomarkers Lactuca sativa L., Lemna minor, and Artemia salina indicated that, although they were similar to photolysis in terms of efficiency, the effluents generated when employing the doped catalysts showed lower levels of toxicity, with the best results achieved for the material doped with 0.005 mol L-1 of Bi, with a toxicity level approximately 40% lower. Photoelectrocatalysis proved to be the most efficient CIP degradation technique. The highest degradation rate was observed for materials doped with 0.005 mol L-1 of Bi, with an efficiency of 46%, which is 1.4 times more efficient than photolysis. These results demonstrate that materials doped with low amounts of Bi can be effectively used as photoanodes for drug degradation, as their performance is superior, and the final product generated exhibits low toxicity to living organisms